Debt Management and Economic Stabilization - Brockie, Melvin D. (Quarterly Journal of Economics, 1954)
I. Introduction, 613. — II. Federal Reserve's control of member bank reserve positions, 613. — III. Treasury-Federal Reserve discord and “accord,” 615. — IV. Recent monetary and debt management proposals, 619. — V. Further suggestions regarding economic stabilization and suitable debt management procedures, 621.